SEASONAL DIAMETER INCREMENT FOR 7 SPECIES FROM AN OMBROPHYLLOUS MIXED FOREST, SOUTHERN STATE OF PARANÁ, BRAZIL - Figueiredo Filho, Afonso; Rode, Rafael; Figueiredo, Décio José de; Machado, Sebastião do Amaral (Floresta, 2008)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Seasonal diameter increment for seven species from an Ombrophyllous Mixed Forest located in São João do Triunfo, South of the State of Paraná was evaluated from September 1998 to September 2005 (a seven year period) using dendrometric bands. Sixty-one Araucaria angustifolia trees, 19 Nectandra grandiflora, 12 Campomanesia xanthocarpa, 10 Cinnamomum vesiculosum, 10 Prunus brasiliensis, 9 Ocotea porosa and 8 Matayba elaeagnoides were studied. Within each species measurements were taken at the end of each season. The diameter increment was evaluated using Randomized Complete Block Design by species, by year, and even by season. The analyses were carried out for six years (September, 1999 to September, 2005) and led one to conclude that diameter increment rate in the summer was greater than in the spring, followed by autumn and winter, corresponding to 53, 26, 17 and 4% of the annual yield respectively. Prunus brasiliensis and Nectandra grandiflora showed the highest annual increment rates. The mean annual increments from the six broadleaved studied trees were 0.262 cm, and 0.122 cm for Araucaria angustifolia. Diameter increments correlated to temperature and precipitation, indicated that temperature has higher effect on increment (r = 0.72) than precipitation (r = 0.49).